Diversity, Abundance, Spatial Variation, and Human Impacts in Marine Meiobenthic Nematode and Copepod Communities at Casey Station, East Antarctica - Stark, Jonathan S.; Mohammad, Mahadi; McMinn, Andrew; Ingels, Jeroen (Frontiers in Marine Science, 2020)
The composition, spatial structure, diversity and abundance of Antarctic nematode and copepod meiobenthic communities was examined in shallow (5 – 25 m) marine coastal sediments at Casey Station, East Antarctica. The sampling design incorporated spatial scales ranging from 10 meters to kilometres and included testing for human impacts by comparing disturbed (metal and hydrocarbon contaminated sediments adjacent to old waste disposal sites) and control areas. A total of 38 nematode genera and 20 copepod families were recorded with nematodes being dominant, comprising up to 95% of the total abundance. Variation was greatest at the largest scale (km’s) but each location had distinct assemblages. At smaller scales there were different patterns of variation for nematodes and copepods. There were significant differences between communities at control and disturbed locations. Community patterns had strong correlations with concentrations of anthropogenic metals in sediments as well as sediment grain size and total organic content. Given the strong association with environmental patterns, particularly anthropogenic disturbance, meiofauna may be seen as very useful indicators of natural and anthropogenic environmental changes in Antarctica.